Cosmopolitanism and the Climate Crisis - Bernstein, Alyssa R. (Con-Textos Kantianos. International Journal of Philosophy, 2019)
As awareness of global warming has spread during the past couple of decades and developed into the realization that humanity faces an existential threat, a number of more or less Kantian liberal or cosmopolitan moral and political theorists have attempted to address questions of justice raised by the climate crisis. David Held was among the most prolific and influential of them. Here I discuss Held’s cosmopolitan perspective on climate governance and consider its bearing on certain recent proposals for new institutions, including in particular a proposal offered by John Broome and Duncan Foley for establishing a World Climate Bank (WCB). I argue that such a WCB may be endorsable from Held’s perspective, depending how the initial proposal may get further developed. Held’s approach to politics is similar to Kant’s in certain significant respects, including the role of hope. Both approaches are valuable and important in relation to the climate crisis.